FC 077LONG-TERM SAFETY OF TENAPANOR FOR THE CONTROL OF SERUM PHOSPHORUS IN PATIENTS WITH CKD ON DIALYSIS. (29th May 2021) - Weiner, Daniel; Fishbane, Steven; Lynn, Robert; Yang, Yang; Rosenbaum, David
Abstract: Background and Aims: Tenapanor, a first-in-class, phosphate absorption inhibitor blocks the paracellular absorption of phosphate in the GI tract by local inhibition of the sodium-hydrogen exchanger (NHE3). It therefore provides a novel, non-binder approach for managing hyperphosphatemia. Tenapanor is dosed as one small pill twice daily. In three pivotal trials, tenapanor met its primary phosphorus-lowering outcome. This report evaluates long-term safety data from the longest of these trials. Method: This 52-week study consisted of a 26-week, open-label, randomized treatment period with a 12-week placebo-controlled randomized withdrawal period, followed by a 14-week open label safety extension period. Maintenance dialysis patients with serum phosphorus ≥ 6.0 mg/dL and a 1.5 mg/dL increase in serum phosphorus following phosphate binder washout were randomized 3:1 to receive tenapanor 30 mg twice daily or sevelamer carbonate, dosed per package insert. At end of the randomized treatment period all patients in the tenapanor arm were re-randomized 1:1 to either tenapanor or placebo for the randomized withdrawal period followed by tenapanor for the safety extension period. Sevelamer was used as a safety control for comparisons of serious adverse events/hospitalizations to tenapanor. Results: Tenapanor was generally well tolerated, with diarrhea the only adverse event reported by >5% of patients during the randomized treatment period. Diarrhea was typically mild-to-moderate in severity, transient, and occurred more commonly during the randomized treatment period than the randomized withdrawal or safety extension periods. Rates of serious adverse events leading to hospitalization were higher in patients treated with sevelamer than tenapanor (35.8% vs 24.6%). The highest reported percentages of serious adverse events were infections and infestations (16.1% vs 9.3%) cardiac disorders (8.0% vs 5.7%), respiratory, thoracic and mediastinal disorders (8.8% vs 5.5%), and metabolism and nutritional disorders (7.3% vs 3.6%) for sevelamer and tenapanor, respectively. Adverse events leading to death were higher in patients treated with sevelamer than tenapanor (3.6% vs 2.9%). Conclusion: Among maintenance dialysis patients with hyperphosphatemia, tenapanor, a novel, non-binder, phosphate absorption inhibitor that blocks paracellular absorption of phosphorus with a one tablet twice daily dose, has an acceptable safety profile, and, if approved, may offer a new approach to the treatment of hyperphosphatemia.